GWAS of bone size yields twelve loci that also affect height, BMD, osteoarthritis or fractures - Unnur Styrkarsdottir (Nature Portfolio, 2019)
Size and shape of bones are important for height and body shape. Here, Styrkarsdottir et al identify 12 loci in a GWAS for bone area derived from DXA scans and show that these loci associate with other bone-related phenotypes including osteoarthritis, height, bone mineral density and risk of hip fracture.